Decision Support System for Selecting Student Thesis Study Fields - Muhamad Al-Fajar Ananda Ulsa; Renny Puspita Sari; Ferdy Febriyanto (TEPIAN, 2023)
A thesis is a requirement for students to obtain an undergraduate degree. These requirements apply to the Department of Information Systems at the University of Tanjungpura. The first step in completing a thesis is to determine a title associated with the field of study, which is provided by the Department of Information Systems at the University of Tanjungpura. In the Information Systems Department, the process of determining the field of thesis study is done manually, leading to confusion and difficulty in selecting the appropriate field for students' theses. A decision support system has been developed to facilitate students in determining the field of study for their theses. The system utilizes the profile-matching method with the aim of providing mathematical and accurate recommendations for the thesis's field of study. The system testing employs the black box testing method.